Influence of stretching exercise on performance and movement technique during drop jumps - Fantini, C. H.; Menzel, H. J.; Chagas, M. H. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to verify the influence of a single flexibility training session on drop jump performance (vertical velocity at take off) and movement technique (joint angles and joint angular velocities). Thirty male subjects performed two drop jumps before and after four sets of quadriceps static stretching. A control session was made without stretching. The results showed an increase in ground contact time, an increase in knee and ankle joint flexion as well as an increase in knee maximal angular velocity during the eccentric and concentric phases. However, these changes in the movement technique have not affected the performance.